1995
DOI: 10.3109/00365549509018982
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-related Infections by Hansenula anomala in Children

Abstract: During August and September, 1992, we experienced 4 cases of Hansenula anomala (H. anomala, synonym Pichia anomala) fungemia in immunocompromised patients. Two patients had been suffering from a malignant disease, 3 of them had received broad-spectrum antibiotics and a central venous catheter (CVC) had been inserted in all of them. H. anomala was isolated as the sole pathogen from all 4 patients. Three of them responded favorably to fluconazole after withdrawal of the catheter, but one failed. H. anomala shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 11 publications
0
16
0
3
Order By: Relevance
“…Candida albicans was the most common pathogen (4/5) in our series. Recent reports suggest either increased recognition or increased frequency of infection with Hansenula anomala as in one of our patients [22]. The incidence of positive blood cultures in Aspergillus spp.…”
Section: Discussionmentioning
confidence: 50%
“…Candida albicans was the most common pathogen (4/5) in our series. Recent reports suggest either increased recognition or increased frequency of infection with Hansenula anomala as in one of our patients [22]. The incidence of positive blood cultures in Aspergillus spp.…”
Section: Discussionmentioning
confidence: 50%
“…Molecular epidemiologic studies suggested a common source. An additional seven outbreaks of C. pelliculosa (P. anomala) fungemia in either neonatal or pediatric intensive care units, affecting patients ranging in number from 2 to 24 (4,7,59,67,69,102,111), and two outbreaks involving adult patients (4 and 8 patients, respectively) (37, 54) have been reported in the literature. In several of these outbreaks, analyses of the epidemic curve and molecular epidemiologic markers suggested a common exogenous source for C. pelliculosa (P. anomala) fungemia.…”
Section: Resultsmentioning
confidence: 99%
“…The exact reasons for these changes are not completely clear. In some cases, they may be related to specific medical interventions, such as antifungal prophylaxis [10] and the use of medical devices [11][12][13] . However, in the majority of cases, they seem to be a consequence of changes in the host, with more severe immunosuppression [14] .…”
Section: Introductionmentioning
confidence: 99%